2021
DOI: 10.1080/17425255.2021.1955856
|View full text |Cite
|
Sign up to set email alerts
|

Effect of oral semaglutide on the pharmacokinetics of thyroxine after dosing of levothyroxine and the influence of co-administered tablets on the pharmacokinetics of oral semaglutide in healthy subjects: an open-label, one-sequence crossover, single-center, multiple-dose, two-part trial

Abstract: A. Baekdal (2021) Effect of oral semaglutide on the pharmacokinetics of thyroxine after dosing of levothyroxine and the influence of co-administered tablets on the pharmacokinetics of oral semaglutide in healthy subjects: an open-label, one-sequence crossover, single-center, multipledose, two-part trial,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 31 publications
1
10
0
1
Order By: Relevance
“…After treatment, serum Tg and TgAb levels in both groups decreased, and the control group had lower results than the observation group, suggesting that levothyroxine tablets combined with iodine-131 could eliminate normal follicular cells and reduce the synthesis and level of Tg, thereby reducing antigen stimulation and TgAb level. This is consistent with the research results by Liang [ 20 , 21 ]. In addition, there was no significant difference in the adverse reactions of the two groups of patients, which indicated that levothyroxine tablets combined with iodine-131 would not increase the adverse reactions of thyroid cancer patients.…”
Section: Discussionsupporting
confidence: 94%
“…After treatment, serum Tg and TgAb levels in both groups decreased, and the control group had lower results than the observation group, suggesting that levothyroxine tablets combined with iodine-131 could eliminate normal follicular cells and reduce the synthesis and level of Tg, thereby reducing antigen stimulation and TgAb level. This is consistent with the research results by Liang [ 20 , 21 ]. In addition, there was no significant difference in the adverse reactions of the two groups of patients, which indicated that levothyroxine tablets combined with iodine-131 would not increase the adverse reactions of thyroid cancer patients.…”
Section: Discussionsupporting
confidence: 94%
“…The synthetic levothyroxine it contains is identical to the thyroxine naturally secreted by the thyroid gland and is converted to T3 in peripheral organs, which then exerts its specific effects by binding to T3 receptors [ 16 ]. The main component of levothyroxine sodium tablets is levothyroxine, and the binding rate to specific transporters is extremely high, about 99.97% [ 17 ]. The binding of this protein to hormones is not a covalent structure, so the plasma concentrations of bound and free hormones can be continuously and rapidly exchanged to maintain the physiological function of the thyroid, inhibit TSH secretion, reduce tumor cell adhesion, and promote the body's immunomodulatory effects [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Co-administration of oral semaglutide with 600 μg of levothyroxine -an oral medication with similar dosing requirements to semaglutide, namely administration once daily on an empty stomach with a full glass of water, 30-60 min before breakfast [24,75] -increased exposure to thyroxine by 33% (AUC 0-48 h,T4 ), supporting the recommendation to avoid coadministration of oral semaglutide within 30 min of other oral medications [24,74]. No obvious effect on thyroxine exposure was seen with SNAC alone, indicating that the increased exposure may be due to the delayed gastric emptying effect of semaglutide [74].…”
Section: Interactions With Drugs Commonly Administered In Patients Wi...mentioning
confidence: 99%
“…Given the mechanism of action of oral semaglutide [56], which includes delayed gastric emptying [24], a number of studies have assessed the impact of oral semaglutide/SNAC on exposure to other commonly administered oral drugs [71][72][73]. In a pharmacokinetic study, co-administration of oral semaglutide with multiple (five) placebo tablets reduced the absorption of semaglutide [74]. Hence, clinical dosing guidance states that other oral medications should be administered at least 30 min after oral semaglutide [24,74].…”
Section: Interactions With Drugs Commonly Administered In Patients Wi...mentioning
confidence: 99%